Comfort Theory in Practice: Lavender Aromatherapy for Sleep Pattern Disturbance in Hypertensive Older Adults at a Community Health Center - Zafarah Risqi Aulia Rachma; Bagus Dwi Cahyono; Nurul Huda; Nadia Rohmatul Laili; Sri Wahyuni; Kon Alier (Inovasi Lokal, 2026)
Introduction: Hypertension commonly impairs sleep quality among older adults because persistent sympathetic nervous system activation interferes with the physiological relaxation required for sleep initiation and maintenance. Although antihypertensive therapy controls blood pressure, sleep disturbances often persist, highlighting the need for effective non-pharmacological nursing interventions in primary care. This case report aimed to describe the implementation of lavender aromatherapy, guided by Kolcaba's Comfort Theory, in managing sleep pattern disturbances among hypertensive older adults. Methods: A descriptive case report was conducted involving two hypertensive older adults receiving nursing care at the Gadingrejo Health Center, Pasuruan City, Indonesia. Nursing assessment and care were based on the Indonesian Nursing Diagnosis, Intervention, and Outcome Standards (SDKI, SIKI, and SLKI). Lavender aromatherapy was administered using a diffuser containing 50 mL of water and 4–5 drops of lavender essential oil for approximately 60 minutes before bedtime over seven consecutive days, accompanied by sleep hygiene education. Data were collected through interviews, direct observation, physical examination, and nursing documentation. Results: Both participants experienced fewer nocturnal awakenings and reported improved subjective sleep quality after the intervention. One participant also demonstrated resolution of neck pain and dizziness, accompanied by normalization of blood pressure. In the second participant, nocturia remained a persistent factor limiting optimal sleep despite overall improvement. Conclusion: Lavender aromatherapy, integrated within Kolcaba's Comfort Theory, showed potential as a feasible, theory-based nursing intervention for improving sleep comfort in hypertensive older adults in primary care settings. Further studies with larger samples are warranted to confirm its effectiveness.